International law on Arctic search and rescue : and the impact of the Arctic SAR agreement on Icelandic SAR obligations under international law - Viitanen, Leena-Kaisa, 1977- (2013)
Verkefnið er lokað til 31.5.2018. During the past decade or so there has been an increasing interest towards the Arctic region. One of the developments seemingly escalating now is the emergence of a regional legal regime governing the Arctic. A major development regarding this regime was the adoption of the first ever multinational legally binding agreement under the auspices of the Arctic Council in May 2011, when eight Arctic countries, The US, Canada, Russia, Iceland, Denmark, Norway, Sweden and Finland adopted legally binding agreement on Arctic search and rescue at the Nuuk Ministerial Meeting. This master’s thesis examines how the creation of the regional legal system for the Arctic impacts the already existing legal framework. It will specifically consider what direct impact the adoption of the 2011 Arctic SAR Agreement has had on the International search and rescue obligations and what changes it has brought about on the Icelandic law on search and rescue at sea. Áhugi á Norðurslóðum hefur aukist jafnt og þétt síðasta áratug eða svo. Á siðustu árum hefur áhugi fyrir lagasetningu fyrir þetta svæði aukist mjög og hægt er að segja að það sé að myndast svæðisbundinn lagarammi í kringum Norðurheimsskautin. Mikil tímamót urðu í Maí 2011, þegar Norðurheimskautslöndin átta; Bandaríkin, Kanada, Rússland, Ísland, Danmörk, Noregur, Svíþjóð og Finnland samþykktu lagalega bindandi samkomulag um leit og björgun á Norðurslóðum á ráðherrafundi Norðurheimskautsráðsins í Nuuk, Grænlandi. Í þessari ritgerð er leitast við að skoða hvaða áhríf samkomulagið um leit og björgun á Norðurslóðum hefur haft á alþjóðalögin um leit og björgun, en einning verður fjallað um þær breytingar sem samkomulagið hafði á íslensk lög um leit og björgun á sjó.